Designing novel lightweight, high-strength and high-plasticity Tix(AlCrNb)100-x medium-entropy alloys. (February 2020) - Liao, Y.C.; Li, T.H.; Tsai, P.H.; Jang, J.S.C.; Hsieh, K.C.; Chen, C.Y.; Huang, J.C.; Wu, H.J.; Lo, Y.C.; Huang, C.W.; Tsao, I.Y.
Abstract: Due to the demand for reduced energy consumption by transportation vehicles, lighter weight high-entropy alloys (with density comparable to that of commercial Ti alloys around 4.5–5 g/cm 3 ) are attracting more attention in terms of alloy design and application as structural materials. In this study, a nonequiatomic quaternary alloy system, Ti x (AlCrNb)100- x, was designed through the calculation of phase diagrams. Simulation results reveal that a single body-centered cubic (BCC) phase can be formed and can be stable at temperatures above 950 °C. Accordingly, a series of Ti x (AlCrNb)100- x ( x = 45–80) alloys containing a BCC structure were prepared through vacuum arc melting and rapid cooling. The designed alloys can exhibit desirable mechanical properties with high compression yield strength about 1500 MPa, high compression fracture strength about 1800 MPa and high compression plasticity more than 30% at room temperature. Moreover, the Ti65 alloy can demonstrate a tensile strength of 1200 MPa with a tensile elongation of 32%, after a homogenization treatment for 24 h. The specific compression and tensile strength can reach 0.36 and 0.24 GPa cm 3 /g. Highlights: Novel alloys designing of light weight high entropy alloys by calculation of phase diagrams. High strength with high ductility medium-entropy alloys (MEAs). Both of the as-cast and homogenized samples possess BCC structures and perform superior tensile strength as well plasticity.